2024 Decadal Survey for Space and Solar Physics: Space Weather Inputs - Noé Lugaz; Jennifer L. Gannon; Shasha Zou; Steven K. Morley; Huixin Liu; Brett A. Carter; Michael Hapgood (Space Weather)
Abstract The next decadal survey process for space and solar physics will start soon with white papers due during the second half of 2022 and the committees and panels working over all of 2023. Space weather science and operations will play an essential role in this survey. Therefore, the community is invited to prepare white papers and get involved in advancing space weather research and capabilities in the upcoming decades. A summary of the recommendations related to space weather from the last two decadal surveys is also provided.